2020
DOI: 10.1186/s13007-020-00584-7
|View full text |Cite
|
Sign up to set email alerts
|

An improved growth medium for enhanced inoculum production of the plant growth-promoting fungus Serendipita indica

Abstract: Background: The plant endophytic fungus Serendipita indica colonizes roots of a wide range of plant species and can enhance growth and stress resistance of these plants. Due to its ease of axenic cultivation and its broad host plant range including the model plant Arabidopsis thaliana and numerous crop plants, it is widely used as a model fungus to study beneficial fungus-root interactions. In addition, it was suggested to be utilized for commercial applications, e.g. to enhance yield in barley and other speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The flasks were autoclaved at 121 °C for 15–20 min. Media were poured into Petri dishes and prepared for inoculation ( Osman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flasks were autoclaved at 121 °C for 15–20 min. Media were poured into Petri dishes and prepared for inoculation ( Osman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The hyphal bodies were removed by filtering the mixture through a fine mesh sieve. The conidial concentration of the final suspension was determined by direct count using a hemocytometer ( Osman et al, 2020 , El-Saadony et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…For growth tests in liquid medium or on agar plates, those media optimal for the respective species were used. Potato Dextrose Agar (PDA; Carl Roth GmbH, Germany) or potato dextrose medium was used for V. longisporum and F. graminearum , and Vegetable Juice (VJ) medium 45 for S. sclerotiorum and S. indica. For plate experiments, mycelial plugs of identical size were placed in the center of the plate, except for V. longisporum, which was inoculated with 10 μL of spore solution (containing 5000 spores) pipetted in the center of the plate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the cultivation of a Penicillium hordei strain on tulip agar led to the medium-dependant production and isolation of the novel metabolites corymbiferone [ 19 ] and corymbiferan lactones A-D [ 20 ]. Host-derived media have also been successfully applied to enhance the yield of fungal inocula [ 21 , 22 ], to stimulate the production of low abundance metabolites [ 23 ], and to promote novel extracellular enzyme production and enhance protein expression [ 24 , 25 , 26 , 27 ]. In the marine field, the in vitro cultivation of fungi on mussel-derived substrates has been employed to convert agricultural and marine residues into microbial metabolites [ 27 , 28 , 29 , 30 , 31 , 32 ], and a recent study showed that mussel-processing wastewaters were a promising nutritive medium for astaxanthin production by the basidiomycetous species Xanthophyllomyces dendrorhous [ 29 ].…”
Section: Introductionmentioning
confidence: 99%